2021
DOI: 10.1016/j.arbres.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Physical Activity Progression in Patients With COPD

Abstract: JGA had full access to all of the data in the study and takes responsibility for the integrity of the data and the accuracy of the data analysis. MK, HD and JGA drafted the first version of the manuscript; MK, HD, MB and JGA had full access to the data and were responsible for the statistical analysis;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In our study, we were able to identify that people with COPD from profiles 1, 2 and 3 might benefit from pulmonary rehabilitation (exercise, education and psychosocial support) to target their activity-related dyspnoea, impact of disease, lower-limb muscle dysfunction and/or functional status impairment [ 34 ]. Profiles among people with COPD who could benefit from pulmonary rehabilitation and physical activity promotion to address their symptoms, exercise intolerance and functional status impairments have been previously reported [ 8 , 10 , 32 , 35 37 ]. Those in profiles 1 and 3 might also benefit from dietary counselling and calorie restriction plus resistance exercise training [ 38 , 39 ] and referral for comorbidities’ management [ 40 ], due to their high BMI and severity of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we were able to identify that people with COPD from profiles 1, 2 and 3 might benefit from pulmonary rehabilitation (exercise, education and psychosocial support) to target their activity-related dyspnoea, impact of disease, lower-limb muscle dysfunction and/or functional status impairment [ 34 ]. Profiles among people with COPD who could benefit from pulmonary rehabilitation and physical activity promotion to address their symptoms, exercise intolerance and functional status impairments have been previously reported [ 8 , 10 , 32 , 35 37 ]. Those in profiles 1 and 3 might also benefit from dietary counselling and calorie restriction plus resistance exercise training [ 38 , 39 ] and referral for comorbidities’ management [ 40 ], due to their high BMI and severity of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 47 Moreover, a recent study analysing physical activity progression over time identified that a higher mMRC dyspnoea score was independently related to an inactive pattern. 48 These observations are most likely due to the respiratory mechanical constraints resulting from the development of dynamic hyperinflation. 49 , 50 Finally, regarding the independent association between the CAT score and inactivity observed in our study, quality of life was consistently related to physical activity in a former systematic review analysing the determinants and outcomes of physical activity in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Bradley et al [21] reported that neither lung function (FEV 1 % predicted) nor disease severity (BSI score) was correlated with sedentary behaviour in patients with bronchiectasis. Data collected from patients with COPD have shown that physical activity decliners vary from 35% to 59% over time [41,42], but the clinical characteristics could not predict or explain the subsequent patterns of decline, included the number of exacerbations [42][43][44][45]. This indicates that the common clinical and functional assessments are unsuitable for use as indicators of risk of physical activity decline and/or increase in sedentary behaviour, which further highlights the need for further longitudinal and objective assessment in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the common clinical and functional assessments are unsuitable for use as indicators of risk of physical activity decline and/or increase in sedentary behaviour, which further highlights the need for further longitudinal and objective assessment in clinical settings. Moving forward, the whole spectrum of those behaviours must be included, accounting for the potential impacts of psychological, interpersonal, social, and environmental correlates in the assessment [5,42,46].…”
Section: Discussionmentioning
confidence: 99%